Podredumbre del pie del tomate, causada por Fusarium solani (Mart.) Sacc. - Wolcan, Silvia M. (1991)
Fil: Wolcan, Silvia M. Buenos Aires (Provincia). Comisión de Investigaciones Científicas (CIC). La Plata, Buenos Aires, Argentina.